The burg / Nurain Amani Roz Foad ...[et al.] - Roz Foad, Nurain Amani; Mohd Nasir, Asyirah; Rosman, Mohamad Aiman Mustaqim; Sharil Fitri, Muhammad Shafizul Fadzli; Mohd Radhi, Afina Raihana (2023)
‘The Burg’ carries the inspiration and spirit from five members - Mustaqim, Afina, Shafizul, Asyirah and Amani, who are very passionate in establishing a healthy ready-to-eat burger as the business project. With the uprising fast-food options that has become a worldwide culture for people to consume whenever they want something quick and easy to eat, The Burg has taken full consideration to offer healthy frozen burgers that are conveniently easy to prepare where people can easily preheat it in a microwave and enjoy it as much as they want just like the regular burger they enjoy on daily basis. Life gets hectic, with massive pile of works that need to be done, working parents that are barely survival in balancing their work life and kids, university students struggling to make meet ends at the same time hustling in their study field, these undoubtedly give a better reason for a frozen burger that can be prepared in a blink of an eye to fill up their tummies. The prime reason for choosing this product is to encourage Malaysians especially the young folks to switch their choice of burger to a more nutritious burger without compromising their taste as what most people assume regarding frozen burgers. Customer experience with the business’ services is something The Burg constantly look forward to. Since this business is a new one on the market, there are a lot of factors will need to take into account to ensure that The Burg can compete with other frozen burger companies and meet customer demand. This is because there are many people working in the business world, particularly the fast food services that are saturating the food market. The patties for are sourced from 100% halal suppliers to convince most customers that are Muslims in this country. In the short term, eating fast food affects blood sugar and blood pressure, causes inflammation, and may result in undernutrition. A diet heavy in fast food may eventually cause problems with digestion, immunity, inflammation, heart health and obesity. Hence, this golden opportunity was taken to take part in the food industry to cater their wants with a better alternative of burgers that suits the nutrients they need. Ramly Burger is chosen as the business model to guide The Burg in pursuing the frozen burger business. The approximate budget to start The Burg as a new business in the field is RM49 546.45. The Burg hopes that this business will become recognized for its frozen burgers in the neighborhood and elsewhere, as well as being able sometimes to offer better services. Last but not least, as a newbie in the frozen food industry, The Burg enjoys serving as a model for those looking to launch frozen food enterprises, particularly in the fast-food industry.